2014
DOI: 10.1101/gad.236414.113
|View full text |Cite
|
Sign up to set email alerts
|

Small but sturdy: small RNAs in cellular memory and epigenetics

Abstract: Cells in multicellular organisms have distinct identities characterized by their profiles of expressed genes. Cell identities can be stable over a long time and through multiple cellular divisions but are also responsive to extracellular signals. Since the DNA sequence is identical in all cells, a “cellular memory” of expression profiles is achieved by what are defined as epigenetic mechanisms. Two major molecular principles—networks of transcription factors and maintenance of cis-chromatin modifications—have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 73 publications
1
41
0
4
Order By: Relevance
“…Warto zaznaczyć, iż zarówno zmiany epigenetyczne o charakterze metylacji DNA, jak i zmiany w obrębie białek histonowych będą mogły wpływać na ekspresję informacji genetycznej także poprzez dodatkowy mechanizm powiązany z bezpośrednim wpływem na aktywność w komórkach specyficznej grupy cząste-czek regulatorowych, jakimi są małe interferencyjne RNA. Na uwagę zasługują głównie małe niekodujące cząsteczki RNA z grupy mikroRNA (miRNA) oraz z grupy bogatych w elementy transpozycyjne cząste-czek niekodujących RNA związanych z białkami PIWI (piRNA) [2,31,32,33].…”
Section: Adp-rybozylacja Ubikwitynacja I Sumoilacja Histonówunclassified
See 2 more Smart Citations
“…Warto zaznaczyć, iż zarówno zmiany epigenetyczne o charakterze metylacji DNA, jak i zmiany w obrębie białek histonowych będą mogły wpływać na ekspresję informacji genetycznej także poprzez dodatkowy mechanizm powiązany z bezpośrednim wpływem na aktywność w komórkach specyficznej grupy cząste-czek regulatorowych, jakimi są małe interferencyjne RNA. Na uwagę zasługują głównie małe niekodujące cząsteczki RNA z grupy mikroRNA (miRNA) oraz z grupy bogatych w elementy transpozycyjne cząste-czek niekodujących RNA związanych z białkami PIWI (piRNA) [2,31,32,33].…”
Section: Adp-rybozylacja Ubikwitynacja I Sumoilacja Histonówunclassified
“…Cząsteczki piRNA występują w tzw. klastrach piRNA, które cechuje obecność znacznej ilości różnych rodzajów elementów transpozycyjnych, w związku z czym klastry piRNA pełnią rolę w regulacji ich aktywności [32,33]. Proces dojrzewania piRNA oraz tworzenia kompleksów piwipiRISC odbywa się w cytoplazmie, skąd następnie są one transportowane do jądra komórkowego [33].…”
Section: Micrornaunclassified
See 1 more Smart Citation
“…miRNAs are widely expressed in various body fluids, including blood (plasma, blood platelet, red blood cells and nucleated blood cells) and urine, and are not degraded by endogenous RNA polymerases (11). In addition, numerous reports have indicated that blood miRNAs function as signaling molecules in intercellular signaling pathways (12,13). miRNAs serve crucial functions in multiple cardiovascular cell processes, including development, proliferation, migration, apoptosis, metabolism, damage, regeneration, repair and phenotype change.…”
Section: Introductionmentioning
confidence: 99%
“…1 The inheritance of epigenetic information is achieved through a variety of mechanisms, including non-coding RNAs, 2 post-translational histone modification, 1 and DNA methylation in some organisms. 3 In recent years, non-coding small RNAs have been shown to be key regulators of epigenetic information, playing critical roles in controlling gene expression in response to external cues, by facilitating changes in genome architecture to alter transcriptional programs 4 and protecting host genomes from foreign nucleic acids by silencing transposable elements [5][6][7][8] and viruses.…”
Section: Introductionmentioning
confidence: 99%